Taurine bromamine: A potent oxidant of tryptophan residues in albumin - Ximenes, Valdecir Farias [UNESP]; da Fonseca, Luiz Marcos [UNESP]; de Almeida, Ana Carolina [UNESP] (Elsevier B.V., 2011)
Taurine is the most abundant free amino acid in leukocytes and can react with HOBr to produce taurine bromamine (Tau-NHBr). The aim of this study was to assess the ability of Tau-NHBr to oxidize tryptophan, either free or as a residue in albumin. We have demonstrated that Tau-NHBr is a powerful oxidant for tryptophan. Importantly, in comparison to taurine chloramine, HOCl or HOBr, Tau-NHBr exhibits a degree of selectivity for tryptophan. Oxidation of albumin by Tau-NHBr resulted in emission of light, and the quantum yield was more than 10-fold more efficient than that of the other oxidants. The fluorescence band corresponding to oxidized albumin (lambda(ex) 350/lambda(em) 450), which is characteristic of the formation of formylkynurenine, was significantly higher in reactions using Tau-NHBr. Excitation of the fluorescent probe 8-anilino-1-naphthalenesulfonate at 295 nm was used to assess the depletion of tryptophan residues in albumin. Results from this experiment further supported a higher efficiency of oxidation of tryptophan residues by Tau-NHBr. Other parameters of protein oxidation, including cysteine depletion and formation of carbonyl groups, were not significantly different between the oxidants tested. In conclusion, these results indicate that Tau-NHBr has a higher affinity for tryptophan residues in proteins. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Tryptophan; Taurine chloramine; Taurine bromamine; Hypochlorous acid; Hypobromous acid; Albumin